2009
DOI: 10.3354/meps07860
|View full text |Cite
|
Sign up to set email alerts
|

Role of salinity in the susceptibility of eelgrass Zostera marina to the wasting disease pathogen Labyrinthula zosterae

Abstract: Eelgrass wasting disease, caused by the net-forming protist Labyrinthula zosterae, is suspected as the causative agent in the North Atlantic population declines of the temperate seagrass Zostera marina in the 1930s, as well as in more recent localized die-offs. During these declines, populations of eelgrass in low salinity areas were less likely to decline and quicker to recover. The goal of this study was to understand the relationships between eelgrass wasting disease and salinity, and how phenolic acids, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 32 publications
0
33
1
Order By: Relevance
“…becomes inactive below 10 PSU (Young 1943, Muehlstein et al 1988, Martin et al 2009). Additionally, laboratory experiments have found a correlation between salinity and lesion coverage (Burdick et al 1993), and a positive linear relationship between salinity and L. zosterae lesion area (McKone & Tanner 2009), further supporting the hypothesis that low salinity is a limiting factor for L. zosterae infection. A yearlong field survey showed that wasting disease increased during increasing salinity events in a Z. marina meadow in Great Bay, New Hampshire, USA, and that prolonged disease was sustained during salinities above 20 PSU (Burdick et al 1993).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…becomes inactive below 10 PSU (Young 1943, Muehlstein et al 1988, Martin et al 2009). Additionally, laboratory experiments have found a correlation between salinity and lesion coverage (Burdick et al 1993), and a positive linear relationship between salinity and L. zosterae lesion area (McKone & Tanner 2009), further supporting the hypothesis that low salinity is a limiting factor for L. zosterae infection. A yearlong field survey showed that wasting disease increased during increasing salinity events in a Z. marina meadow in Great Bay, New Hampshire, USA, and that prolonged disease was sustained during salinities above 20 PSU (Burdick et al 1993).…”
Section: Introductionmentioning
confidence: 67%
“…This suggests that the production of inhibitory compounds is not induced by a high pathogen pressure, as previously suggested (Buchsbaum et al 1990, Vergeer et al 1995, but rather that Z. marina contains inhibitory compounds that function as a constitutive defense. In contrast, the most studied potential defense compounds against L. zosterae infection so far, the phenolic acids, have been shown to increase in infected seagrass shoots, and to correlate with lesion size in laboratory infection experiments (McKone & Tanner 2009). In addition, trans-cinnamate 4-monooxygenase, an enzyme for phenol synthesis, is upregulated in L. zosteraeinoculated shoots (Brakel et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…seem to be very common in northern Z. marina beds [62]. This implies that L. zosterae may not be pathogenic under non-or low-stress conditions [60,63,64], possibly as a result of low pathogenicity, a strong defence reaction of the host, or both. Given our finding of additional putative pathogens in Z. marina beds, we may have to revisit the pathology of Z. marina, and perhaps also of seagrasses in general.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, subtidal eelgrass populations in the Baltic remained relatively unaffected . One hypothesis is that brackish water protects against L. zosterae because it slows down growth and replication of the endophyte (McKone & Tanner 2009). However, the fact that the very saline Mediterranean as well as the Pacific coast of North America remained unaffected (Cotton 1933) contradicts this hypothesis.…”
Section: Introductionmentioning
confidence: 99%